Pengaruh Perceived Ease Of Use, Perceived Usefulness, dan Trust terhadap Intention To Use Mobile Payment pada Pria dan Wanita - Christina Sudyasjayanti; Aiman Fauzi Gadi (Jurnal Mirai Management, 2022)
Mobile payment is a phenomenon that cause major impact in people payment activities. The aim of this research was to determine the relationship between perceived ease of use, perceived usefulness and trust in the intention to use mobile payments for men and women. Individual motivating factors in using mobile payment are different, including differences in individual encouragement in using mobile payment applications for men and women. The approach of this research was quantitative with multiple regression analysis method which is carried out three times to determine differences in intention to use between men, women, and both. The sample used in this research amounted to 170 samples with the characteristics of mobile payment users who live in the city of Surabaya or DKI Jakarta, are at least 21 years old, and are male or female. The results of this study indicate that the variables of perceived ease of use, perceived usefulness and trust affect the intention to use mobile payment. However, there are differences between men and women in their intention to use mobile payments. The result indicate that difference factors in intention to use mobile payment between men and women is perceived ease of use variable doesn’t have a significant effect on regression tests with male data only with 0,006 of significance value, then when the regression test is carried out with female data only the results shown are that trust variable doesn’t affect intention to use mobile payment for female respondents with 0,130 of significant value. Keywords: Mobile payment, perceived ease of use, perceived of usefulness, trust, intention to use